2021
DOI: 10.1097/ju.0000000000001399
|View full text |Cite
|
Sign up to set email alerts
|

Nonantibiotic Strategies for the Prevention of Infectious Complications following Prostate Biopsy: A Systematic Review and Meta-Analysis

Abstract: Purpose: We identify which nonantibiotic strategies could reduce the risk of infectious complications following prostate biopsy. Materials and Methods: We performed a literature search on MEDLINEÒ, EmbaseÒ and the Cochrane Database for randomized controlled trials (inception to May 2020) assessing nonantibiotic interventions in prostate biopsy. Primary outcome was pooled infectious complications (fever, sepsis and symptomatic urinary tract infection) and secondary outcome was hospitalization. Cochrane risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
107
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 16 publications
4
107
0
8
Order By: Relevance
“…However, the difference in risk between with and without periprostatic nerve block appears to be low. 9 Moreover, a prospective study 10 reported that the 10-core biopsy procedure was painful in 131 of 275 patients (47.6%), uncomfortable but not painful in 93 (33.8%), and neither painful nor uncomfortable in 51 (18.6%). Together these findings indicate that local anesthesia in this setting is painful, and some TR-PBx patients do not experience pain caused by the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the difference in risk between with and without periprostatic nerve block appears to be low. 9 Moreover, a prospective study 10 reported that the 10-core biopsy procedure was painful in 131 of 275 patients (47.6%), uncomfortable but not painful in 93 (33.8%), and neither painful nor uncomfortable in 51 (18.6%). Together these findings indicate that local anesthesia in this setting is painful, and some TR-PBx patients do not experience pain caused by the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Im Gegensatz dazu war in einer großen kanadischen Kohortenstudie mit mehr als 9000 Patienten Fosfomycin trometamol (Einmaldosierung und Zweimalgabe) mit höheren Infektionskomplikationen als Ciprofloxacin (Einmalgabe oder Prophylaxe über 3 Tage) assoziiert, was gegen die uneingeschränkte Verwendung von Fosfomycin trometamol spricht [23]. In ihrer Durchführungsentscheidung vom Juni 2020 sieht die EU-Kommission einen positiven Nutzen in der Verwendung von Fosfomycin trometamol in der Prophylaxe bei der transrektalen Prostatabiopsie, forderte jedoch zusätzliche pharmakokinetische und pharmakodynamische Daten, um die Verwendung einer zweiten Dosis [14].…”
Section: Introductionunclassified
“…Eine Meta-Analyse mit 7 RCTs konnte zeigten, dass Infektionskomplikationen bei transperinealer Prostatabiopsie signifikant gegenüber dem klassischen transrektalen Verfahren reduziert waren (RR 0,55) [14]. Ferner zeigte die Auswertung einer systematischen Literatursuche mit 165 eingeschlossenen Studien und 162 577 Patienten eine Sepsisrate von 0,1 % für die transperineale und 0,9 % für die transrektale Prostatabiopsie [15].…”
Section: Introductionunclassified
See 2 more Smart Citations